2018
DOI: 10.5312/wjo.v9.i9.165
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injection alonevsadditional physiotherapy treatment in early stage frozen shoulders

Abstract: AIMTo investigate the additional value of physiotherapy after a corticosteroid injection in stage one or two idiopathic frozen shoulders (FSs).METHODSA two center, randomized controlled trial was done. Patients with a painful early stage idiopathic FS were eligible for inclusion. After written consent, patients were randomly allocated into two groups. All patients received an ultrasound-guided intra-articular corticosteroid injection. One group underwent additional physiotherapy treatment (PT) and the other gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…Of the 65 eligible studies, a total of 34 studies 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 were included in pairwise meta-analyses with a total of 2402 participants with frozen shoulder. Duration of symptoms ranged from 1 month to 7 years and length of follow-up from 1 week to 2 years, with most follow-up occurring at 6 weeks, 12 weeks, and 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 65 eligible studies, a total of 34 studies 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 were included in pairwise meta-analyses with a total of 2402 participants with frozen shoulder. Duration of symptoms ranged from 1 month to 7 years and length of follow-up from 1 week to 2 years, with most follow-up occurring at 6 weeks, 12 weeks, and 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the main characteristics of the included studies. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Resultsunclassified
“…Koh et al, in a systematic review of RCTs, report corticosteroid injections as superior to placebo and physiotherapy in the short term (12 weeks) [43] Furthermore, a meta-analysis of nine RCTs with 453 patients found steroid injections equally as effective as physiotherapy; the authors recommend single steroid injection as the first line treatment in ACS [44]. However, several other RCTs have shown that steroid injections used as adjuncts to physiotherapy provide greater improvement in symptoms when compared with physical therapy alone [29,45,46].…”
Section: Intra-articular Steroid Injectionsmentioning
confidence: 99%
“…In addition, US is an inexpensive and non-invasive technique, and it can be widely used in patients with non-MRI-compatible implants. US can not only help diagnose ACS, but also guide intra-articular corticosteroid injections, which can effectively control inflammation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%